405 Impact of hyperthermic intraperitoneal chemotherapy (HIPEC) on tumor microenvironment (TME) in ovarian cancer – a subanalysis from a Phase I clinical trial. (13th November 2020) - Dellinger, T; He, T; Lee, P; Guo, W; Cho, H; Wu, X; Liang, W; Schmolze, D; Razavi, M; Ruel, N; Han, E; Wakabayashi, M; et al.
Abstract : Background: Immunogenic cell death has been suggested as a mechanism for HIPEC, through the release of heat shock proteins, and resulting in activation of tumor-specific T cells. Methods: This is a subgroup analysis of a Phase I trial using HIPEC with cisplatin 75 mg/m2 at time of optimal cytoreduction. Metastatic tumors from nine ovarian cancer patients were collected intraoperatively before and after HIPEC. Differentially expressed genes and pathways of pre- and post-HIPEC tumors were analyzed via whole-transcriptome sequencing (WTS). Immunofluorescent (IF) staining and multispectral imaging were used to determine composition and PD-1 expression of CD8+ and conventional CD4+ tumor-infiltrating lymphocytes (TILs), using antibodies against CD8, FOXP3, PD-1, and pancytokeratin (to distinguish cancer islands from stroma). Kaplan-Meier and log-rank tests compared the overall and progression free survivals (PFS) of patients with low versus high%PD-1 changes, based on dichotomization with respect to the median%PD-1 change. Results: Heatshock proteins comprised the top differentially upregulated genes in HIPEC-treated tumors. Gene set enrichment analysis revealed significant upregulation of immune pathways, including antigen processing/presentation. IF staining demonstrated increased%PD-1 in cancer islands of CD8+ and CD4+ TILs after HIPEC. In stroma, the largest%PD-1 change occurs in an exceptional responder (PFS, OS 5 years), while the lowest%PD-1 change occurred in a poor responder. Kaplan-Meier curves demonstrate superior PFS in patients with high stromal PD-1 changes in TILs after HIPEC. Conclusions: Increased PD-1 expression after HIPEC suggests early HIPEC-induced T cell activation, and is associated with improved survival, implicating a potential future role for PD-1 inhibitors following HIPEC in ovarian cancer.